Seasonal variation in gonad physiology indicates juvenile breeding in the Saker Falcon (Falco cherrug). Issue 2 (May 2021) - Dixon, Andrew; Ward, Janelle; Ichinkhorloo, Sarangerel; Erdenechimeg, Tuvshinjargal; Galtbalt, Batbayar; Davaasuren, Batmunkh; Bold, Batbayar; Batbayar, Nyambayar
We describe seasonal changes in the physiology of reproductive organs of Saker Falcons electrocuted on an electricity power line in Mongolia. Macroscopic examination of the gonads revealed asymmetry in testes size, with bias to the left body side. This asymmetry declined with seasonal increase in testes size during the main egg-laying period of the breeding season. In females, 91% possessed both left and right ovaries ( N  = 161); there was no visible oviduct associated with the right ovary and it was smaller than the functional left ovary. Both ovaries showed seasonal development in size, becoming larger during the peak egg-laying period. Hierarchical preovulatory follicular development was recorded in two females, with ca. 5 mm difference in the diameter of sequential follicles. Both sexes developed brood patches during the main incubation period, with adults more likely to exhibit brood patches than juveniles. Among juveniles, at least 82% of females and 91% of males were non-breeders without brood patches. The high electrocution rate at our studied power line provided a rare opportunity to examine the non-breeding component of the Saker population. Juveniles predominated in the non-breeding population during the main egg-laying period (89%, N  = 65), with the proportion of adults electrocuted being significantly lower among females. Only a small proportion of juvenile females exhibited gonadal evidence of breeding, consistent with the low observed frequency of juvenile breeders at nests. The demographic composition of the non-breeding population is consistent with female mortality rates exceeding that of males, and potentially indicates incipient population decline.